2019
DOI: 10.1038/s41588-018-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new therapeutic targets for osteoarthritis through genome-wide analyses of UK Biobank data

Abstract: Osteoarthritis is the most common musculoskeletal disease and the leading cause of disability globally. Here, we perform a genome-wide association study for osteoarthritis (77,052 cases and 378,169 controls), analysing 4 phenotypes: knee osteoarthritis, hip osteoarthritis, knee and/or hip osteoarthritis, and any osteoarthritis. We discover 64 signals, 52 of them novel, more than doubling the number of established disease loci. Six signals fine map to a single variant. We identify putative effector genes by int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
419
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 416 publications
(443 citation statements)
references
References 54 publications
(69 reference statements)
9
419
0
15
Order By: Relevance
“…We identified 36 genes for which the experimental perturbation induces changes in the opposite direction to molecular differences between high-grade and low-grade cartilage ( Supplementary Table 8), notably including knock-down of IL11. Variation in IL11 is associated with increased risk of hip osteoarthritis 9 , and the gene is up-regulated in osteoarthritis knee tissue 36 , with a similar trend observed here. IL11 is a cytokine with a key role in inflammation, and monoclonal anti-IL11 antibodies have been developed for use in several diseases.…”
Section: Candidate Therapeutic Compoundssupporting
confidence: 83%
See 3 more Smart Citations
“…We identified 36 genes for which the experimental perturbation induces changes in the opposite direction to molecular differences between high-grade and low-grade cartilage ( Supplementary Table 8), notably including knock-down of IL11. Variation in IL11 is associated with increased risk of hip osteoarthritis 9 , and the gene is up-regulated in osteoarthritis knee tissue 36 , with a similar trend observed here. IL11 is a cytokine with a key role in inflammation, and monoclonal anti-IL11 antibodies have been developed for use in several diseases.…”
Section: Candidate Therapeutic Compoundssupporting
confidence: 83%
“…We used a soft-thresholding centroid-based method, PAMR 13 , to develop a gene expression-based classifier capable of distinguishing between the two cartilage clusters. We identified 7 genes, the expression levels of which could be combined to predict cluster assignment for each patient sample (Figure 4a, Supplementary Figure 9): MMP1, MMP2, and MMP13, known to be involved in cartilage degradation 14 ; IL6, a proinflammatory cytokine; CYTL1, a cytokine-like gene, loss of which has been found to augment cartilage destruction in surgical osteoarthritis mouse models 15 ; APOD, a component of high-density lipoprotein found to be strongly up-regulated by retinoic acid 16 , which is in turn regulated by ALDH1A2 17 , an osteoarthritis risk locus 9,18 ; and C15orf48, with currently unknown function. Notably, the posterior probabilities for cluster assignment output by the classifier captured the main continuous spectrum of variation in this tissue (Figure 4b).…”
Section: -Gene Classifier Predicts Clusteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of OA is dependent on multiple factors, with both environmental and genetic components [2,3]. To discover genes and underlying disease pathways genetic studies, such as large genome wide association studies (GWAS), have been performed that identified compelling OA risk single nucleotide polymorphisms (SNPs) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%